A robust centralized SMES controller design based on WAMS considering system and communication delay uncertainties - Saejia, Mongkol; Ngamroo, Issarachai (My University, 2011)
It is well known that the communication delay due to the phasor measurement in wide area monitoring system (WAMS) as well as various system operating conditions such as heavy line flows and unpredictable network structures, may deteriorate the wide-area stabilizing control effect. To overcome this problem, the inverse input and output multiplicative model is proposed to represent unstructured uncertainties due to system operations and communication delay in the robust centralized damping controller design of superconducting magnetic energy storage (SMES) based on WAMS. The structure of centralized controller for SMES is the practical 1st-order lead/lag compensator. To automatically tune the control parameters, the optimization problem based on the enhancement of damping performance and system robust stability margin is achieved by particle swarm optimization. Simulation studies in the West Japan six-area interconnected system confirm that the proposed robust SMES centralized controller is superior to the conventional SMES centralized controller in terms of damping performance and robustness against system and time delay uncertainties. © 2010 Elsevier B.V.
Keywords: Inter-area oscillation; Phasor measurement unit; Superconducting magnetic energy storage; System uncertainty; Wide area measurement system